Saddlestrapping - Singh, Sarjinder (Nonlinear Analysis: Modelling and Control, 2009)
A method of weighted bootstrapping in the presence of auxiliary information has been studied and named as saddlestrapping because there exists a saddlepoint. Comparisons of saddlestrapping with the bootstrapping under different situations are performed and discussed. FORTRAN code for doing bootstrapping and saddlestrapping are provided. A huge scope of further studies has been suggested.